From doctor's orders to nurse's notes: A study of the career shift phenomenon among medical doctors in Tacloban City - Labarda, Meredith del Pilar (Animo Repository, 2007)
The youth, who are living at their particular time of growth, have been recognized by the Church not only as the future of the Church but as the present of the Church. Considering the importance of young people in the Church, youth ministry has already been discussed a lot in the Korean Church but contemporary spirituality for Korean youth, which is capable of leading them in these post-modern times, has not been brought into existence and developed. Korean youth ministry is mainly focused on activities. The faith of Korean Catholic young people is becoming superficial, unrealistic and irrelevant to their daily life. A spirituality lived by young people themselves would be the most probable answer to the problem of Korean youth ministry because we can see the appearance of a vivid Church through the people who strive to live their own spirituality which they have chosen to live. It is for this reason that this study was undertaken. The study seeks to define a youth spirituality which takes into consideration the developmental needs of young people and the core of Christian faith, which is the doctrine of the Trinity in order to make it valuable and stable. The researcher conducted a questionnaire survey of 100 young Catholics in the Archdiocese of Daegu. The researcher compared the survey results with the response of the developmental theories applicable to the youth and then tried to find out how the developmental theories can resonate with the Catholic theological understanding of the Trinity. Analyzing the results of the questionnaire survey, and articulating psychological factors and principal elements on the mystery of the blessed Trinity pertinent to the needs of the young in Daegu, the researcher discovered there is an obvious convergence area of the three sources of the study, which is communion, the cardinal point in defining a youth spirituality inspired by the Trinity. Hence, it is important for young people to live in the community based on the communion of love and unity which reflects the communion of the Trinity in growing towards the fullness of life. The faith-filled community with which Sunday school students can share their life and faith will be the most effective and powerful instrument for their ideal development in faith. Therefore, young people should be encouraged to build a community based on the communion of the Triune God since they are also agents and co-workers in the Church's mission (Ecclesia in Asia, art. 47). More specifically, Sunday school students as members of their Sunday school and family should live a communion of life and love in the God of communion in those communities first. The doctrine of the Trinity is the normative Christian model for understanding who God is and consequently where we are coming from and where we are headed. This is why the study tried to anchor the spirituality of youth on the mystery of the Trinity. On the other hand, human beings are created in Gods very own image and likeness (Gn 1:26-27), and therefore, it is an indisputable fact that we can discover the image of the triune God even in the life of the young in their particular stage of development. Young people would be able to live more vivid daily life and faith life when they discover and experience by themselves, the triune God engraved in their hearts and when they strive to resemble the Trinity. The researcher believes that the following words of the scriptures will encourage adolescents to live the Trinitarian spirituality. Do not conform yourself to this age but be transformed by the renewal of your mind, iii that you may discern what is the will of God, what is good and pleasing and perfect (Rom 12:2)